(untitled) (Práxis Educativa, 2017)
The objective of this study was to map out and analyze students’ production involving the Physical Education and Inclusion theme, from theses and dissertations coming from Postgraduate programs in Brazil. It is an exploratory research of the literature systematic review type. We found 73 studies in total – 60 masters theses and 13 doctorate dissertations, defended in 33 Brazilian universities from 2002 to 2015. The analyzed studies were organized into 10 thematic categories. We verified that the researches have concentrated on the educational process of the P.E teacher. Although the number of publications has been growing in recent years, it is necessary to decentralize the studied research themes, in order to adopt a systemic view and provide actions that give support to new ways of thinking about inclusion in the context of Physical Education in schools in Brazil. Keywords: Physical Education in school. Inclusive education. Scientific production.